2013
DOI: 10.1088/0952-4746/33/3/605
|View full text |Cite
|
Sign up to set email alerts
|

Mapping radon-prone areas using γ-radiation dose rate and geological information

Abstract: Identifying radon-prone areas is key to policies on the control of this environmental carcinogen. In the current paper, we present the methodology followed to delineate radon-prone areas in Spain. It combines information from indoor radon measurements with γ-radiation and geological maps. The advantage of the proposed approach is that it lessens the requirement for a high density of measurements by making use of commonly available information. It can be applied for an initial definition of radon-prone areas in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Radon levels in the environment can show important spatial variations on a regional or local scale. It has been recognized that this lateral variability is primarily attributed to geological parameters which control the radon source-term and/ or the radon migration in the ground (Appleton et al, 2015;Bossew, 2015;Drolet et al, 2013Drolet et al, , 2014García-Talavera et al, 2013;Gruber et al, 2013;Hahna et al, 2015;Ielsch et al, 2001Ielsch et al, , 2002Ielsch et al, , 2010Kropat et al, 2014;Scheib et al, 2013;Smethurst et al, 2008;Tondeur et al, 2015;Zhukovsky et al, 2012). Therefore, the knowledge of uranium and/or radium contents in rocks is of primary importance to determine the radon source term.…”
Section: Introductionmentioning
confidence: 99%
“…Radon levels in the environment can show important spatial variations on a regional or local scale. It has been recognized that this lateral variability is primarily attributed to geological parameters which control the radon source-term and/ or the radon migration in the ground (Appleton et al, 2015;Bossew, 2015;Drolet et al, 2013Drolet et al, , 2014García-Talavera et al, 2013;Gruber et al, 2013;Hahna et al, 2015;Ielsch et al, 2001Ielsch et al, , 2002Ielsch et al, , 2010Kropat et al, 2014;Scheib et al, 2013;Smethurst et al, 2008;Tondeur et al, 2015;Zhukovsky et al, 2012). Therefore, the knowledge of uranium and/or radium contents in rocks is of primary importance to determine the radon source term.…”
Section: Introductionmentioning
confidence: 99%
“…According to Bossew et al ( 2013 ), “Qualitatively, this concept denotes areas where observed or expected values of a 222 Rn-related variable are high with respect to reference values or with respect to the mean over the domain”. In general, radon-prone areas are identified according to two main strategies: (a) direct measurements of indoor radon concentration and (b) indirect methods including soil gas radon survey and gamma-dose assessment based on γ-spectrometry from laboratory, field and aerial surveys all implying the existence of a more or less known transfer factor from the crustal environment into the buildings (Dubois and Bossew 2006 ; García-Tavalera et al 2013 ). Since each single methodology is usually not sufficient to the scope, hybrid approaches are often used suggesting the need for integrated information as an optimal tool for radon area classification.…”
Section: Introductionmentioning
confidence: 99%
“…How ever, both ig nore nat u ral re al ity, as the main spa tially con trol ling fac tor is ge ol ogy. Also us ing poly gons rep re sent ing geo log i cal units as es ti ma tion sup ports has in deed been con sid ered, e. g. in Spain [13].…”
Section: Es Ti Ma Tion Of Ra Don Pri or Ity Ar Easmentioning
confidence: 99%